Bone healing of mandibular critical-size defects in spontaneously hypertensive rats - Veronica Kei Len Chin; Adriana Shinagawa; Maria da Graca Naclerio-Homem (Sociedade Brasileira de Pesquisa Odontológica, 2013)
Few articles have shown changes in bone metabolism caused by hypertension. The objective of this study was to investigate the relationship between hypertension and bone healing. Circular critical-size defects 5 mm and 2 mm in diameter were created, respectively, on the left and right side of the mandible in 40 spontaneously hypertensive and 40 control Wistar-Kyoto rats. Five animals from each strain were killed 2, 3, 5, 10, 15, 30, 60 and 90 days after surgery. The macroscopic evaluation showed great mandibular angle deformation on the left side and non-healed defects on both sides and groups. Histological evaluation revealed similar bone healing on both sides, with initial necrosis in the central area, and fibrosis and angiogenesis within the first 5 days. From the 10th postoperative day on, the newly formed bone displayed progressive thickening until the 90th postoperative day, when the defect margins presented a compact bone structure. Furthermore, the statistical analysis of the histometric data did not reveal any significant hypertension effect on bone healing in the defect area. These results suggest that bone healing was not different between spontaneously hypertensive rats and control rats.